Improving Students’ Religious Tolerance Through Civic Education: A Strategic Approach - Nurbayti, Fidah; Purnama, Dona; Putri, Mas Fierna Janvierna Lusie (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Indonesia, as a country rich in religious diversity, faces a major challenge due to rising religious intolerance in the education sector. This study explores the issue of religious intolerance in the educational environment and assesses the important role of Pancasila and Citizenship Education (PPKn) in building character, with reference to scientific journals and relevant reports. The research findings indicate that religious intolerance in schools is caused by a lack of understanding of Pancasila values, excessive influence of social media, limited interfaith dialogue, and teachers' limited ability to manage diversity. PPKn plays a crucial role in fostering tolerant attitudes through cognitive, affective, and psychomotor aspects. However, traditional teaching methods, which emphasise effective learning models, need to integrate cognitive, affective, and psychomotor elements. Implementation requires the development of an inclusive curriculum, enhancing teachers' capabilities, creating a supportive school environment, and collaborating with various relevant parties